2018
DOI: 10.1111/bjd.17208
|View full text |Cite
|
Sign up to set email alerts
|

Risk of first‐time and recurrent depression in patients with psoriasis: a population‐based cohort study

Abstract: Psoriasis was independently associated with risk of depression. These results may help clinicians identify particularly high-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
(23 reference statements)
0
35
0
1
Order By: Relevance
“…The worldwide prevalence rates of psoriasis range from 0.9–8.5% in adults and 0–2.1% in children (2). Although this condition rarely poses a threat to life, the irritation, pain and especially the aberrant appearance make these patients susceptible to psychological problems, such as anxiety and depression (3,4). With recent advances in the understanding of psoriasis, an increasing number of therapies have emerged, however a high recurrence rate persists.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence rates of psoriasis range from 0.9–8.5% in adults and 0–2.1% in children (2). Although this condition rarely poses a threat to life, the irritation, pain and especially the aberrant appearance make these patients susceptible to psychological problems, such as anxiety and depression (3,4). With recent advances in the understanding of psoriasis, an increasing number of therapies have emerged, however a high recurrence rate persists.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 5-HT is also a main factor in depression, which is one of the main comorbidities of psoriasis. In fact, it has been reported that psoriasis is associated with a 39% increase in depression and 31% increase in anxiety [120], while a recent population-based cohort study revealed that the highest risk for depression occurred for mid-aged patients with severe forms of psoriasis and patients with a prior history of depression [121]. Moreover, the cytokine theory of depression suggests that depression and other mental disorders have hormonal and biochemical components, and might involve inflammation processes [122].…”
Section: The Role Of Serotonin In Psoriasismentioning
confidence: 99%
“…Depression and anxiety are common comorbidities among psoriasis and PsA patients which may be a result of psychosocial difficulties as well as common inflammatory pathways. [1][2][3][4][5][6][7] However, little is known about whether systemic treatments for psoriasis and PsA are associated with an increased risk of anxiety and depression, and whether these risks differ between the various treatments. Short-term clinical trials reported a somewhat elevated risk of depression in apremilast users, resulting in a label warning.…”
Section: Introductionmentioning
confidence: 99%
“…Apremilast is an oral medication used to treat psoriasis and psoriatic arthritis (PsA) by inhibiting phosphodiesterase‐4, a protein found in immune cells associated with inflammation. Depression and anxiety are common comorbidities among psoriasis and PsA patients which may be a result of psychosocial difficulties as well as common inflammatory pathways . However, little is known about whether systemic treatments for psoriasis and PsA are associated with an increased risk of anxiety and depression, and whether these risks differ between the various treatments.…”
Section: Introductionmentioning
confidence: 99%